2020
DOI: 10.1111/tbed.13496
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian 2014 porcine epidemic diarrhoea virus outbreak: Important risk factors that were not considered in the epidemiological investigation could change the conclusions

Abstract: The introduction and spread of porcine epidemic diarrhoea virus (PEDV) in North America resulted in significant death loss in the swine industry. As the industry learned how to manage this disease, many new risks were identified, including the potential for feed and feed ingredients to become contaminated and spread PEDV.In addition, biosecurity practices were reevaluated and strengthened throughout the industry. At the time of the outbreak epidemiologists did not understand, as well as they are understood tod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Future studies are also needed to explore the contribution of movements to slaughterhouses, especially when pig is redirected to other slaughterhouses (i.e. slaughter not able to slaughter all animals) or send back to the farm of origin, this is very common in the US (Russell et al, 2020). Another limitation was the number of farms missing geographic locations, since this analysis will be re‐run be the local veterinary services yearly, once this farm location become available the results will be updated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are also needed to explore the contribution of movements to slaughterhouses, especially when pig is redirected to other slaughterhouses (i.e. slaughter not able to slaughter all animals) or send back to the farm of origin, this is very common in the US (Russell et al, 2020). Another limitation was the number of farms missing geographic locations, since this analysis will be re‐run be the local veterinary services yearly, once this farm location become available the results will be updated.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are also needed to explore the contribution of movements to slaughter houses, especially when pig are redirected to other slaughter houses (i.e., slaughter not able to slaughter all animals) or send back to the farm of origin, this is very common in the US, however little is known relevance in spreading disease back to the farm, however there is some early discussion about it (Russell et al, 2020).…”
Section: Considerationsmentioning
confidence: 99%
“…However, the widespread use of SDPP has been compromised in the North American pork industry because a SDPP source contaminated with Porcine Epidemic Diarrhea Virus (PEDV) was implicated as the cause of the initial outbreak (Dee et al, 2014;Pasick et al, 2014;Pasma et al, 2016;Aubry et al, 2017;Perri et al, 2018). However, important risk factors were not considered in the epidemiological investigation of the 2014 Canadian PEDV outbreak, which makes this claim questionable (Russell et al, 2020). Furthermore, the lack of direct experimental evidence (Gerber et al, 2014), along with rigorous risk assessments that have shown that PEDV and other swine viruses are inactivated during processing SDPP (Sampedro et al, 2015), and the lack of causing an African Swine Fever Virus (ASFV) infection in naïve weaned pigs by feeding diets containing ASFV-contaminated liquid plasma (Blázquez et al, 2020), indicate that more thorough review of relative risks and benefits of using spray-dried animal plasma in swine feeds is warranted.…”
Section: The Need To Converge the Diverging One Health Components Of Animal Feedsmentioning
confidence: 99%
“…, 10 represent the parameters to be estimated, constant C is the drift term, and ε it is the random term. Several studies have discussed the risk factors associated with the prevalence of animal diseases, such as farm management practices (18), forest (19), soil water content (20), and water source (21). Evidence suggests that the spread of epidemic diseases is closely related to environmental factors, humans, and animals (22).…”
Section: Measurements and Statistical Analysismentioning
confidence: 99%